1994
DOI: 10.1016/0168-6445(94)90084-1
|View full text |Cite
|
Sign up to set email alerts
|

Progress in biopulping of non-woody materials: Chemical, enzymatic and ultrastructural aspects of wheat straw delignification with ligninolytic fungi from the genus Pleurotus

Abstract: During screening of basidiomycetes for wheat straw delignification, considerable lignin degradation with a limited attack to cellulose was attained with Pleurotus eryngii. Straw solid-state fermentation (SSF) was optimized, and the enzymatic mechanisms for lignin degradation were investigated. No lignin peroxidase was detected under liquid or SSF conditions, but high laccase and aryl-alcohol oxidase levels were found. The latter enzyme has been fully characterized in PI. eryngii and it seems to be involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 16 publications
1
56
0
1
Order By: Relevance
“…Continued expression of POH2 and POH3 by emerging aerial hyphae would coat them with the observed hydrophobic rodlet layer. As has been surmised for SC3 of S. commune (Wosten et al, 1994b) and ABH3 of A. bisporus (Lugones et al, 1998), secreted POH2 and POH3 could also play a role in facilitating lignin degradation, an important activity of P. ostreatus (Martinez et al, 1994).…”
Section: Discussionmentioning
confidence: 98%
“…Continued expression of POH2 and POH3 by emerging aerial hyphae would coat them with the observed hydrophobic rodlet layer. As has been surmised for SC3 of S. commune (Wosten et al, 1994b) and ABH3 of A. bisporus (Lugones et al, 1998), secreted POH2 and POH3 could also play a role in facilitating lignin degradation, an important activity of P. ostreatus (Martinez et al, 1994).…”
Section: Discussionmentioning
confidence: 98%
“…5 A). Analytical IEF showed that the isoenzymes have slightly different PI, 3.75 for MP-1 and 3.65 for MP-2 (Fig. 5B), which may explain their separation on Mono-Q.…”
Section: Properties Of the Mp Isoenzymesmentioning
confidence: 99%
“…Some species, including Pleurotus eryngii, have the capacity to remove lignin preferentially (i.e., with limited degradation of cellulose) [ 11, a characteristic relevant to biotechnological delignification processes for feed production 121 and paper-pulp manufacture [3].…”
mentioning
confidence: 99%
“…P. ostreatus is widely reported to be a selective degrader of lignin [30,53]. A systematic screening of ligninolytic fungi [54] reported that lignin was preferentially degraded from wheat straw by P. ostreatus. White rot fungi, of which P. ostreatus is an example, possess unique ligninolytic enzymes that completely degrade lignin to CO 2 and H 2 O [55].…”
Section: Ligninmentioning
confidence: 99%